A Study to Assess the Impact of Comorbid Poly Cystic Ovarian Syndrome on Maternal Outcomes among Postnatal Mothers - A Retrospective Cohort Study (International Journal of Food and Nutritional Sciences, 2022)
Background: The ovaries are a female's reproductive organs that regulate the menstrualcycle and the secretion of hormones such as estrogen, progesterone, inhibin, relaxin, andothers. The overabundance of eggs causes the ovary to enlarge and release high amounts ofmale hormone, resulting in infertility. PCOS is a hormonal condition that affects almost 5-10% of women in their childbearing ages (12 to 45-years). In this condition, the hormones ofa woman go out of balance which makes various symptoms, including anovulation, irregularmenstrual cycle, difficulty conceiving, weight gain, acne, and hirsutism.Aim: To assess the maternal outcomes of PCOS and non PCOS among postnatal mother.Materials and Methods: A retrospective cohort study was carried out in St, Joseph Hospitalat Puducherry. A total of 132 (PCOS 66 and NON PCOS 66) samples were selected based onthe inclusion criteria through convenience sampling technique. The data were collected frommedical record department using check list and collected data were analyzed by descriptiveand inferential statistics. Statistical analysis was carried out using the Statistical Package forSocial Sciences (SPSS, version 16).Result: The study result revealed that women with PCOS are at increased risk of adversematernal outcomes especially Pregnancy Induces Hypertension, Gestational DiabeticMellitus, Thyroid problem, extended labour duration, Caesarean section ,low Apgarscore(